Characterization of metabolic fate of phellodendrine and its potential pharmacological mechanism against diabetes mellitus by ultra‐high‐performance liquid chromatography‐coupled time‐of‐flight mass spectrometry and network pharmacology. (20th July 2021) - Zhang, Feng‐Xiang; Yuan, Yu‐Lin‐Lan; Cui, Shuang‐Shuang; Li, Min; Li, Rui‐Man
Abstract : Rationale: Characterizing the functional mechanism of quality control marker (Q‐marker) was of great importance in revealing the primary pharmacological mechanism of herbs or the other complex system, and drug‐related metabolites always contribute to the pharmacological functions. Cortex Phellodendri was used as a core herb in the treatment of diabetes mellitus (DM). As a Q‐marker of Cortex Phellodendri, the role of phellodendrine in DM was still unclear. Thus, the characterization of phellodendrine‐related metabolites in vivo and the subsequent induced functional mechanism exerted great importance in elucidating the anti‐DM mechanism of Cortex Phellodendri. Methods: An ultra‐high‐performance liquid chromatography‐coupled time‐of‐flight mass spectrometry (UHPLC/Q‐TOF MS) method was developed to profile metabolites of phellodendrine in rats. The potential pharmacological mechanism against DM was predicted by network pharmacology. Results: A total of 19 phellodendrine‐related metabolites were screened out in rats for the first time. Among them, M4, M5, M9, and M12 were regarded as the primary metabolites. Meanwhile, phase I metabolic reactions of hydroxylation, demethylation, and isomerization and phase II reactions of glucuronidation and sulfation occurred to phellodendrine; glucuronidation and hydroxylation were the two main metabolic reactions. Moreover, the potential targets of phellodendrine and three main metabolites (M4, M5, and M12 ) were predicted by a network pharmacological method, and they mainly shared 52 targets, including PDE5A, CHRNA3, SIGMAR1, F3, ESR1, DRD1, DRD2, DRD3, and DRD4. Furthermore, Kyoto Encyclopedia of Genes and Genomes pathway analysis showed that calcium signaling pathway, cGMP‐PKG signaling pathway, and cAMP signaling pathway were regarded as the core mechanism of phellodendrine to treat DM. Conclusion: The metabolic feature of phellodendrine in vivo was revealed for the first time, and its anti‐DM mechanism information for further pharmacological validations was also supplied. It also gave a direction to further elucidation of pharmacological mechanism of Cortex Phellodendri in treating DM.